Demolition technology of buildings and structures of industrial enterprises - Osipov А.; Syhyda, V. (Ways to Improve Construction Efficiency, 2019)
The article discusses the prerequisites and features of the demolition of industrial buildings and structures on the example of a machine-building complex, which was in a dilapidated state, with a view to new construction of the administrative-office-commercial complex.